Comparison of the Incidence of Cardiovascular Diseases in Weight Groups with Healthy and Unhealthy Metabolism - Wang W (Dove Medical Press, 2021)
Wenqiang Wang,1,* Jia He,1,* Yunhua Hu,1 Yanpeng Song,2 Xianghui Zhang,1 Heng Guo,1 Xinping Wang,1 Mulatibieke Keerman,1 Jiaolong Ma,1 Yizhong Yan,1 Jingyu Zhang,1 Rulin Ma,1 Shuxia Guo1,3 1Department of Public Health, Shihezi University School of Medicine, Shihezi, Xinjiang, People’s Republic of China; 2Department of Social Work, The First Affiliated Hospital of Shihezi University Medical College, Shihezi, Xinjiang, People’s Republic of China; 3Department of NHC Key Laboratory of Prevention and Treatment of Central Asia High Incidence Diseases, The First Affiliated Hospital of Shihezi University Medical College, Shihezi, Xinjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuxia GuoDepartment of Public Health, The Key Laboratory of Preventive Medicine, Building No. 1, Shihezi University School of Medicine, Suite 721, Beier Road, Shihezi, 832000, Xinjiang, People’s Republic of ChinaTel +86-1800-9932-625Fax +86-993-2057-153Email gsxshzu@sina.comRulin MaDepartment of Public Health, The Key Laboratory of Preventive Medicine, Building No. 1, Shihezi University School of Medicine, Suite 816, Beier Road, Shihezi, 832000, Xinjiang, People’s Republic of ChinaTel +86-1330-9930-561Fax +86-993-2057-153Email marulin@shzu.edu.cnBackground: We aimed to identify the relationship between metabolically healthy obesity (MHO), a special subtype of obesity, and the incidence of cardiovascular disease (CVD) in rural Xinjiang.Methods: Body mass index (BMI) and the Joint Interim Statement criteria were utilized to define obesity and metabolic status, respectively. A baseline survey was conducted between 2010 and 2012. The cohort was followed-up until 2017, including 5059 participants (2953 Uyghurs and 2106 Kazakhs) in the analysis.Results: During 6.78 years of follow-up, 471 individuals developed CVD, 10.8% (n=545) of whom were obese, and the prevalence of MHO and MHNW was 5.2% and 54.5%, respectively. Compared with metabolically healthy normal weight subjects, the subjects with MHO had an increased risk of CVD (hazard ratio [HR]=1.76, 95% confidence interval [CI]: 1.23− 2.51), while the metabolically unhealthy obesity (MUO) group had an even higher risk (HR=3.80, 95% CI: 2.87− 5.03). Additionally, there were sex differences in the relationship between BMI-metabolic status and incident CVD (Pinteraction =0.027). Compared with the subjects with MHO, those with MUO had an increased risk of CVD (HR=1.84, 95% CI: 1.26− 2.71).Conclusion: MHO was associated with a high risk of CVD among adults in rural Xinjiang. In each BMI category, metabolically unhealthy subjects had a higher risk of developing CVD than did metabolically healthy subjects.Keywords: metabolically healthy obesity, cardiovascular disease, rural areas, epidemiology